Design Criterion for Vibrations Due to Walking - Allen, D.E.; Murray, Thomas M. (Engineering Journal, 1993)
A design criterion for walking vibrations of broader application than previous criteria is proposed for steel floor or footbridge structures. The criterion is based on the dynamic response of steel structures to walking forces, as well as the sensitivity of occupants to vibration motion. The criterion is applicable to structures with natural frequencies below 9 Hz, where resonance can occur with a harmonic of the step frequency, but is extended beyond 9 Hz where footstep impulse response becomes important.